2012
DOI: 10.1002/pmic.201200053
|View full text |Cite
|
Sign up to set email alerts
|

Nonculture‐based identification of bacteria in milk by protein fingerprinting

Abstract: Traditional methods for bacterial identification include Gram staining, culturing, and biochemical assays for phenotypic characterization of the causative organism. These methods can be time-consuming because they require in vitro cultivation of the microorganisms. Recently, however, it has become possible to obtain chemical profiles for lipids, peptides, and proteins that are present in an intact organism, particularly now that new developments have been made for the efficient ionization of biomolecules. MS h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 27 publications
(39 reference statements)
1
24
0
Order By: Relevance
“…It has been shown that one loopful of bacterial cells per spot, or 1 mL of suspended solution (e.g., E. coli, E. faecalis), is sufficient for registering good quality spectra [1,8]. In the case of IC MALDI analysis of bacteria cell taken directly from a biological sample (blood, milk) the minimal value is 10 3 -10 5 cells per μL [8,9].…”
Section: Bacteria Culturementioning
confidence: 99%
See 3 more Smart Citations
“…It has been shown that one loopful of bacterial cells per spot, or 1 mL of suspended solution (e.g., E. coli, E. faecalis), is sufficient for registering good quality spectra [1,8]. In the case of IC MALDI analysis of bacteria cell taken directly from a biological sample (blood, milk) the minimal value is 10 3 -10 5 cells per μL [8,9].…”
Section: Bacteria Culturementioning
confidence: 99%
“…In addition, one of the advantages of IC MALDI method is the fact that only one (single) colony is needed for microbiological analysis [1,8]. Moreover, some released protocols enable direct IC MALDI analysis of bacteria cells from infected blood [8] or milk [9]. This procedure is based on analysis of the unique protein profile of a microorganism, known as molecular fingerprint (MF) [1,9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in the last few years comparative proteomics was used to evaluate milk proteome profiles during acute and chronic phases of bacterial intramammary infection. The results of these researches provide the important information for therapy of these conditions (Addis et al 2011, Kim et al 2011, Barreiro et al 2012, Chiaradia et al 2013.…”
Section: Introductionmentioning
confidence: 99%